One year negative appendicectomy rates at a district general hospital: A Retrospective Cohort Study. (July 2016) - Lim, Jeffrey; Pang, Queenie; Alexander, Roderick
Abstract: Introduction: There is no defined 'acceptable' Negative Appendicectomy Rate (NAR) in the UK. Despite advances in radiology and predictive scoring systems, appendicitis remains a clinical diagnosis but inevitably some patients will have an entirely normal appendix removed. We sought to define our local practice and results. Methods: A one year retrospective observational study was performed in our institution on all appendicectomies performed on an emergency basis. Cases were identified with the hospital electronic theatre record system and histopathology reports were retrieved and analysed. Results: 390 patients were identified over a one year period and split into two groups. Group A (n = 128) was defined as those patients who had no evidence of appendiceal pathology or tissue, giving a NAR of 32.8%. Group B (n = 262) comprised patients whose appendices had any histopathological finding other than normal. Our NAR was not found to be significantly different when compared to a recent large published series (p = 0.711). Within six months, Group A had 19 (14.8%) emergency readmissions compared to 25 (9.54%) in Group B. This was not found to be statistically significant on Fisher's exact testing (p = 1.00). Discussion: Our NAR of 32.8% is higher than expected but comparable to those previously published. Although this did not have a significant impact on patient morbidity as shown by our re-admission rates, revision of our current policy to remove the appendix should no other pathology be identifiable may improve outcomes. Highlights: Our institution has a negative appendicectomy rate (NAR) of 32.8% which is at the upper limit of reported rates. Reassuringly, patients who had undergone negative appendicectomy did not have an increased length of stay or readmission rate. Revising our policy to remove the macroscopically normal appendix in the absence of other pathology may help lower our NAR.